Employee welfare and stock price crash risk - Ben-Nasr, Hamdi; Ghouma, Hatem (Journal of Corporate Finance, 2018)
We examine whether employee welfare practices are associated with future stock price crash risk. Two competing hypotheses were tested: the stakeholder theory hypothesis & the agency theory hypothesis. According to the stakeholder hypothesis, if strong commitment to employee well-being genuinely aims at strengthening the firm's reputation in the market, enhancing the shareholders' engagement, avoiding costly strikes, and boosting the employees' productivity, higher level of employee welfare would be expected to mitigate stock crash risks. On the contrary, the agency theory predicts that, if managers attempt to use generous employee welfare plans to reduce the likelihood that the employees blow the whistle on the management wrongdoings, better employee welfare would likely be associated with higher crash risk. We find robust evidence supporting the agency theory thesis: high levels of employee welfare standards contribute to stock price crash risk. This finding is consistent with the view that employee welfare plans form a powerful strategy that can help managers in their bad-news-hoarding activities (withholding bad news from investors). Moreover, earnings management and the likelihood of whistleblowing appear to be the channels through which employee welfare impacts stock price crash risk. Our evidence further shows that the positive relation between employee welfare and crash risk is stronger for labor intensive firms and industries, in more regulated labor markets, and in less competitive product markets. Furthermore, this positive relationship is more pronounced in poorly governed firms and in countries with poor investors' protection and lower disclosure requirements.